2020
DOI: 10.1007/s11263-020-01383-2
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the Robustness of Semantic Segmentation Models with Respect to Common Corruptions

Abstract: When designing a semantic segmentation model for a real-world application, such as autonomous driving, it is crucial to understand the robustness of the network with respect to a wide range of image corruptions. While there are recent robustness studies for full-image classification, we are the first to present an exhaustive study for semantic segmentation, based on many established neural network architectures. We utilize almost 400,000 images generated from the Cityscapes dataset, PASCAL VOC 2012, and ADE20K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 67 publications
(68 reference statements)
0
24
2
Order By: Relevance
“…Further experiments also distort the test samples to see the effect of each distortion on the performance. The chosen distortions were based on [23]. Before discussing the results, the dataset and distortions are explained in detail.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Further experiments also distort the test samples to see the effect of each distortion on the performance. The chosen distortions were based on [23]. Before discussing the results, the dataset and distortions are explained in detail.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…A simple way to improve the robustness of a machine learning model is data augmentation [61]. However, even though corrupted data can enhance the robustness of CNN models in semantic segmentation [62], introducing corrupted data into the training domain largely diminishes the model accuracy on uncorrupted data.…”
Section: Model Robustnessmentioning
confidence: 99%
“…While CNNs focus on textures [20], Transformers put more importance on the object shape [3,55], which is more similar to human vision [20]. For semantic segmentation, ASPP [7] and skip connections [60] were reported to increase the robustness [36]. Further, Xie et al [86] showed that their Transformer-based architecture improves the robustness over CNN-based networks.…”
Section: Related Workmentioning
confidence: 99%
“…Previous works on semantic segmentation with Transformer backbones usually exploit only local information for the decoder [80,86,96]. In contrast, we propose to utilize additional context information in the decoder as this has been shown to increase the robustness of semantic segmentation [36], a helpful property for UDA. Instead of just considering the context information of the bottleneck features [6,7], DAFormer uses the context across features from different encoder levels as the additional earlier features provide valuable low-level concepts for semantic segmentation at a high resolution, which can also provide important context information.…”
Section: Daformer Network Architecturementioning
confidence: 99%